"It's about getting the best bang for your buck": Exploring local councils' perceptions about providing exercise infrastructure in public parks. (5th August 2020) - Scott, Taryn; Lole, Lisa; Oorloff, Anthea; Aprile, Kerry
Abstract: Issue addressed: Growing evidence suggests that public parks enable physically active communities; however, little is known of the impact of council‐provided exercise facilities in outdoor green spaces, and the challenges of providing this infrastructure at a local level. This paper sought to describe some of the factors, as perceived by local government area (LGA) council representatives within Queensland, Australia, that influence community use of, as well as council provision for, weight‐bearing outdoor fitness station infrastructure in public parks. Methods: A nested mixed‐methods study was employed, comprised of a survey sent to council representatives for all 78 Queensland LGAs ( Stage 1 ), and follow‐up interviews to elicit further insights into the provision of infrastructure in public parks ( Stage 2 ; n = 7). Perceptions around participants' corporate role in the provision of outdoor fitness stations were the focus of analyses. Findings: A thematic analysis described themes of: Moderating public attitudes and motivation ; The flow of information; Supporting an active community ; Return on investment ; and Safety, complianceand climate . Provision of equipment was influenced by the perception that it represented poor value for money, in terms of the desired outcome of increased physical activity, especially when compared with other types of infrastructure (particularly, walking trails); however, opinions about this lack of use outdoor exercise equipment were most often based on anecdotal evidence. Conclusions: Councils are motivated to support active communities. They would benefit from better access to information about park usage, strategies for marketing healthy living initiatives and data about the economic benefits of parks. So what?: The current study explores the perspectives of LGA professional "gatekeepers, " who develop and maintain public physical activity facilities. Their insights are essential to better understand the practicalities of delivering desirable urban green spaces for physically active communities.